Study of PD-L1 Expression in Tumours Based on Site and Histology of Tumour – The Experience of a Tertiary Referral Laboratory - Pant, Vinita; Harlalka, Munmun (Asian Pacific Journal of Cancer Biology, 2023)
Background: PD-L1 IHC test is used as a predictive biomarker using FDA-approved assays to select patients likely to benefit from immunotherapy in several advanced-stage tumors. We aim to present our data regarding the prevalence and expression pattern of PD-L1 across various tumors based on site and histology and compare them with those of the reported literature. Material and Methods: A retrospective study of 301 cases of various tumors at different sites was done for PD-L1 IHC using the 22С3 pharmDx assay on the recommended platform. Results: Out of 237 non small cell lung carcinoma cases, 14.7% were squamous and 85.2% were of nonsquamous histotype, with adenocarcinomas comprising the majority (82.2%). Fifty-seven percent of non small cell lung carcinoma was PD-L1 positive, 28.6% showed high expression. Sixty percent of the squamous and 56.4% of the non-squamous histotypes showed positive immunoexpression. Amongst non-squamous types, 56.4% of adenocarcinomas and 66.6% of sarcomatoid carcinomas were positive. At metastatic sites, 54.3% of on small cell lung carcinoma were positive. In head and neck squamous cell carcinoma, the majority (10/11) of cases were from the oral cavity; 81.8% of total cases were positive, 27.2% were strong expressors. For other sites, the number of cases showing PD-L1 immunopositivity is as follows: oesophageal squamous cell carcinoma (2/6), gastric adenocarcinoma (2/6), triple negative breast carcinoma (0/3), urothelial carcinoma (2/5), gall bladder (2/5), pancreatico-biliary (2/11), and colorectal (2/17) adenocarcinomas. In these tumors, PD-L1 immunoexpression did not differ significantly by age or gender. Conclusion: Our study showed PD-L1 immunopositivity in 57% of non small cell lung carcinoma and 81.8% of head and neck squamous cell carcinoma, which is comparable to international studies. Further studies with larger sample sizes are needed to see their expression pattern in tumors at other sites and with different histologies.